Chromosomal studies of five species of the marine fishes from the Paranaguá bay and the karyotypic diversity in the marine teleostei of the brazilian coast - Cipriano, Roger Raupp; Fenocchio, Alberto Sérgio; Artoni, Roberto Ferreira; Molina, Wagner; Noleto, Rafael Bueno; Kantek, Daniel Luis Zanella; Cestari, Marta Margarete (My University, 2008)
In this study, five species of marine fishes from the Paranaguá Bay in the Brazilian coast were evaluated. Eucinostomus argenteus and Diapterus rhombeus (Gerreidae) presented 48 chromosomes, all of which more acrocentric (FN = 48); Strongylura timucu and S. marina (Belonidae) also presented 48 chromosomes, but with a higher karyotypic complexity than the Gerreidae, 10M+2SM+36A (FN = 60) and 4M+44A (FN = 52), respectively. The fifth species, Mugil curema (Mugilidae), different than the others, presented only 28 chromosomes 20M+4ST+4A (FN = 48). The species presented diversity in the karyotypic macro-structure, which should be relevant for the cytotaxonomy and the evolution of this group of the vertebrate.
Keywords: Marine fishes; Karyotype; Cytotaxonomy; Karyotypic evolution